(untitled) (Global Journal of Science Frontier Research, 2014)
The objective of the present paper is to obtain the reliability of a harvesting system having three unit tractor (T), combine (C) and wagon (W) using supplementary variable technique. For successful operation of the system units T and C must be remain operative while when unit W fails system works partially. Two repairmen are involved in repairing of the system. One of the repairmen (the first) is the foreman (boss) and the other an assistant (apprentice). Whenever unit T and C fails repair is undertaken by boss while repair of the wagon is undertaken by the trainee. If the boss is busy in repairing and at the same time other unit fails then the repair is undertaken by apprentice. With the help of Supplementary variable technique, Laplace transformations and copula methodology, the transition state probabilities, asymptotic behavior, reliability, M.T.T.F. and sensitivity analysis of the system have been evaluated.